On Sánchez: The Improbable Biography of Osvaldo Baigorria (2020)
“How to write a biography after Strafacce?”, doubts Osvaldo Baigorria after having published his own about the vagabond writer Néstor Sánchez (1935 - 2003). In this way, the question enables to reflect on the ethics and the poetics of the biography (How is a life written? Can/Should it be written?) while summoning the incipient local biographical tradition referring to the monumental biography by Ricardo Strafacce on Osvaldo Lamborghini (Osvaldo Lamborghini, una biografía, Mansalva, 2008) as an immediate predecessor. In the present article, the interest is to make a counterpoint between that «exemplary» totalizing biography and the fragmentary biography, deviated, even—in words of his author—«failed», which is Sobre Sánchez (Mansalva, 2012a), as well as analyzing their unique conditions of production, the excessive «affectation» for the life of the Other (biographer / biographic link) and the novel biographical formula resulting from it.